Progress Made in Addressing Emergency Obstetric and Newborn Care Challenges in Zanzibar (Global Journal of Medical Research, 2019)
Abstract not found
Keywords: emergency obstetrics and newborn care; CEmONC; BEmONC; maternal and newborn care; signal functions; maternal mortality